ESSENCE AND SPECIFICS OF FOREIGN LANGUAGE PROFESSIONAL COMPETENCE OF A TEACHER OF TECHNICAL DISCIPLINES - Zelenin, H. (Problems of Engineer-Pedagogical Education, 2023)
The article defines the essence of the concepts “foreign language professional competence of a teacher of technical disciplines” as his/her ability to use a foreign language while performing teaching, educational, research, technical and technological functions of their professional activity: when obtaining, processing and creating materials of subject-information (scientific-technical, scientific-pedagogical and educationalmethodological) nature, while exchanging information with others with the aim of developing and improving his/her own professional performance; “foreign language training of future teachers of technical disciplines” as a comprehensive and systematic specially organized process of an active use of foreign languages by students as a means of mastering and assimilating information relevant to their professional functions while implementing various directions in the training process. The author clarifies the structure and content of the components of foreign language professional competence of teachers of technical disciplines; the clarification was about limiting the list of components and specifying the content of linguistic (related to language and speech); professional-communicative (communicative-pedagogical and communicativetechnical); pragmatic (scientific-pedagogical and scientific-technical) competences in accordance with the professional functions of teachers of technical disciplines. The conclusions of the article highlight the important place of language competence in developing professionally important competences of a higher education student. It was defined as an obligatory key competence of a future specialist, having an interdisciplinary character and serving as the basis for developing professional (general and subject-related) competences. Along with the growing role of a foreign language in language competence, its foreign-language component has been defined. Foreign-language professional competence involves the ability of a specialist in a particular field to use the capabilities of another (foreign) language when performing professional functions: in obtaining and elaborating information, exchanging opinions and information with others for the sake of their own development and improvement of the results of their professional activity. This competence acquires its own specificity regarding the role and importance in the performance of professional functions of pedagogical staff.